Francisella tularensis D-Ala D-Ala Carboxypeptidase DacD Is Involved in Intracellular Replication and It Is Necessary for Bacterial Cell Wall Integrity - Spidlova, Petra; Stojkova, Pavla; Dankova, Vera; Senitkova, Iva; Santic, Marina; Pinkas, Dominik; Philimonenko, Vlada; Stulik, Jiri (Frontiers in Cellular and Infection Microbiology, 2018)
D-alanyl-D-alanine carboxypeptidase, product of dacD gene in Francisella, belongs to penicillin binding proteins (PBPs) and is involved in remodeling of newly synthetized peptidoglycan. In E. coli, PBPs are synthetized in various growth phases and they are able to substitute each other to a certain extent. The DacD protein was found to be accumulated in fraction enriched in membrane proteins from severely attenuated dsbA deletion mutant strain. It has been presumed that the DsbA is not a virulence factor by itself but that its substrates, whose correct folding and topology are dependent on the DsbA oxidoreductase and/or isomerase activities, are the primary virulence factors. Here we demonstrate that Francisella DacD is required for intracellular replication and virulence in mice. The dacD insertion mutant strain showed higher sensitivity to acidic pH, high temperature and high osmolarity when compared to the wild-type. Eventually, transmission electron microscopy revealed differences in mutant bacteria in both the size and defects in outer membrane underlying its SDS and serum sensitivity. Taken together these results suggest DacD plays an important role in Francisella pathogenicity.